Comparative Study on Modern Approaches of Recommender System - Bhanu Prasad, A.; N. Sambasiva Rao, Dr.; Subba Rao, K.; Lakshmi, B (International Journal of Engineering and Technology, 2018)
Recommender system is a kind of tool for filtering information and items of user interest. There are large number of different approaches for filtering data and information. In this paper a comparative study is made on different modern approaches in particular. All the modern approaches along with traditional recommender systems are listed and explained with their merits and demerits. Some common challenges are also addressed in this context.Â